2019
DOI: 10.1002/aoc.5278
|View full text |Cite
|
Sign up to set email alerts
|

Pistacia atlantica leaf extract mediated synthesis of silver nanoparticles and their antioxidant, cytotoxicity, and antibacterial effects under in vitro condition

Abstract: Recently, researchers have investigated the therapeutical properties of metal nanoparticles especially silver nanoparticles in vitro and in vivo conditions. The aim of the experiment was green synthesis and chemical characterization of silver nanoparticles from aqueous extract of Pistacia atlantica leaf (Ag NPs) and evaluation of their cytotoxicity, antioxidant, and antibacterial effects under in vitro condition. Ag NPs were spherical with a size range of 40‐60 nm and characterized using various analysis techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 26 publications
4
22
0
Order By: Relevance
“…The distinction in affectability of Gram-positive and Gram-negative microorganisms to GPE-AgNPs was because of the thickness and the constituents of their membrane structure [33]. The obtained results are found similar with the earlier studies concerning AgNPs synthesized using biological materials [9,52].…”
Section: In Vitro Antibacterial Activitysupporting
confidence: 86%
“…The distinction in affectability of Gram-positive and Gram-negative microorganisms to GPE-AgNPs was because of the thickness and the constituents of their membrane structure [33]. The obtained results are found similar with the earlier studies concerning AgNPs synthesized using biological materials [9,52].…”
Section: In Vitro Antibacterial Activitysupporting
confidence: 86%
“…30 Organic nanoparticles bring promising results, highlighting nanoemulsions that may contain antimicrobial drugs, essential oils with antimicrobial activity, or even the combination of both. [31][32][33][34][35][36][37] Numerous studies bring results when it comes to the use of inorganic nanoparticles using different plant extracts with antimicrobial and healing activities, which include silver nanoparticles, [38][39][40][41][42] titanium nanoparticles, 43,44 gold nanoparticles, [45][46][47] copper nanoparticles, 48,49 zinc nanoparticles, 50 iron nanoparticles 51 and manganese nanoparticles. 52 The aim of this study was to evaluate and validate an aqueous-based chlorhexidine nanoemulsion at 0.25% (NM-Cl).…”
Section: Introductionmentioning
confidence: 99%
“…This result is in agreement with previous studies that used agar disk-diffusion to demonstrate the susceptibility of S. aureus to metallic nanoparticles. [4][5][6][7] However, the inhibitory extent of silver nanoparticles depends to a greater degree on the synthesis approach used, and thus the diameter of the inhibition zone against S. aureus exhibits a variety of concentrations. [4][5][6][7] Furthermore, instead of paper disks, dental porcelain incorporated with one kind of metallic nanoparticle was evaluated by Hashem et al 25 using the disk diffusion, and the authors found that the growth of S. aureus was inhibited effectively.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers favor natural sources in the synthesis of metallic nanoparticles, mainly silver nanoparticles. [4][5][6][7] Metallic nanoparticles are made either of a single element or a combination of elements, eg, nanoparticles can be made solely of silver or a combination of silver and copper elements. Silver nanoparticles can be shaped differently, eg, spheres or rods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation